Water Quality Analysis Based On Diversity and Abundance of Macrozoobenthos In Way Semah River Waters of Pesawaran - Irawan, Tazranisa Indy; Tugiyono, Tugiyono; Suratman Umar; Gregorius Nugroho Susanto (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2024)
River pollution is a major problem in the water quality crisis due to certain factors, including human activities around the river ecosystem which are strongly suspected to be the main cause of the problem. The purpose of this study was to determine the diversity and abundance of macrozoobenthos and the level of water pollution in the Way Semah Pesawaran River. The research was conducted using three indicators of water quality: biological indicators in the form of macrozoobenthos, physical indicators in the form of temperature and brightness, and chemical indicators in the form of pH, DO, and BOD. Sampling was carried out at 3 stations with two points, namely the right bank and left bank points at each station. The method of determining the location and data collection using the purposive sampling method. Based on the results of the analysis of abundance, diversity, uniformity and dominance of macrozoobenthos obtained the ecosystem of Way Semah River waters showed mild to moderate polluted conditions with a range of 1.21 - 1.87